Study results of the stress-strain states of the crown parts of molars restored with composite, ceramic and zirconium onlays - Y.A. Sardykov; M.H. Kryshchuk; O.O. Fastovets; R.Y. Matvieienko (Medičnì Perspektivi)
The relevance of the research is determined by the significant need for effective restorative treatment of caries decayed teeth. The purpose of the study is comparison of the stress-strain states in simulated models of non-homogeneous composite structural elements for typical geometric characteristics of onlays made of composite, ceramic, and zirconium dioxide in the restoration of the decayed mandibular molar. Computer simulation models of biomechanical systems were obtained by digital scanning of the mandibular molar in STEP format. Control was carried out in the form of numerical characteristics and graphical visualization in the EXOCAD program. The numerical method of finite elements, information technologies and program codes of the ANSYS Workbench 12.1 system were used to solve applied problems of biomechanics. After testing the developed discrete models, they were checked for adequacy and coincidence of numerical results in areas of high voltage gradients using the tools and methods of the ANSYS 12.1 code system. The maximum displacements, gradients, and amplitudes of the Mises-equivalent stress in the structural elements of each biomechanical system were evaluated. The stress values were calculated using the method of linear scaling of the results of the numerical solution of the boundary value problems of the theory of elasticity for small deformations to correspond to the functional force load of the mandibular molar of 100 N. The estimated values of the coefficients of the strength reserve of the structural elements were calculated as the ratio of the strength limit values to the maximum calculated values of the Mises-equivalent stress, scaled by a coefficient of 10 for a force load of 100 N. It was established that the largest voltage gradients are registered at the border of the cement layer. However, the nature of force transmission, as well as stress distribution, was different for different structural materials. The maximum stress was observed in the model with a composite onlay in the local area of the surface of the force load in the cement layer. For the ceramic onlay, the maximum stress was found on the lower support surface of contact with the onlay, where its values were 1.4 times higher than on other surfaces. The analysis of the zones of maximum stress for the zirconium onlay revealed their predominant localization in the center of its occlusal surface and in the zone of change in its spatial configuration at the border with cement. The highest stress values, along with the lowest coefficients of safety margin, were found for the molar model restored with a composite onlay, which indicated the lowest endurance of this material to functional load. While the zirconium onlay provided optimal stress distribution and it was characterized by the largest safety factor, which makes this method the most acceptable for molar restoration. The obtained results should be taken into account when choosing a material for the prosthetics of lateral teeth with onlays.